2012
DOI: 10.1111/j.1462-2920.2011.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of novel fusarielins by ectopic activation of the polyketide synthase 9 cluster in Fusarium graminearum

Abstract: Like many other filamentous fungi, Fusarium graminearum has the genetic potential to produce a vast array of unknown secondary metabolites. A promising approach to determine the nature of these is to activate silent secondary metabolite gene clusters through constitutive expression of cluster specific transcription factors. We have developed a system in which an expression cassette containing the transcription factor from the targeted PKS cluster disrupts the production of the red mycelium pigment aurofusarin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 38 publications
2
65
0
Order By: Relevance
“…The gene cluster is also preserved in species of Metarhizium [12], Penicillium, and Colletotrichum (Supplementary Table S1). Besides the PKS (FSL1), the remaining genes are predicted to encode a thioesterase (FSL2), an epimerase (FSL3), a cytochrome P450 oxygenase (FSL4), an enoyl reductase (FSL5), and a transcription factor (FSL7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The gene cluster is also preserved in species of Metarhizium [12], Penicillium, and Colletotrichum (Supplementary Table S1). Besides the PKS (FSL1), the remaining genes are predicted to encode a thioesterase (FSL2), an epimerase (FSL3), a cytochrome P450 oxygenase (FSL4), an enoyl reductase (FSL5), and a transcription factor (FSL7).…”
Section: Resultsmentioning
confidence: 99%
“…FSL6 was excluded from the study as it is unlikely to be part of the conserved fusarielin gene cluster [12]. The generated mutants …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). The highest similarity to PKS10 is exhibited by PKS9, which is involved in the synthesis of fusarielins and is not related to fusarins (33). The analysis of the predicted GzFUS1 (PKS10) polypeptide with the Simple Modular Architecture Research Tool (SMART [see Materials and Methods]) revealed 10 protein domains: KS, AT, DH, MeT, KR, PP, C, AMP, PP, and NAD (see the legend to Fig.…”
Section: Resultsmentioning
confidence: 99%